Modeling and simulation of radiation effects in nanometric volumes of silicon and water - M, Batmunkh; O, Lkhagva; L, Bayarchimeg; D, Erdenebaatar; T, Tuul (Scientific transaction of the National University of Mongolia. Physics, 2022)
Understanding the effects of particle radiation in nanoscale electronic materials and biological materials is particularly important for future long-term space flights, nuclear medicine and nuclear power plants. Heavy charged particles arriving among galactic cosmic rays have powerful damaging actions when they pass through the electronic devices and biological objects. The present study is focused on the Monte Carlo modeling of stochastic energy depositions in charged particle tracks and calculation of absorbed energy within small sample (200 nm) of silicon and liquid water. The silicon is widely used material for memory chips, computer processors, transistors, and all other electronics. The most common biomaterial is liquid water, which accounts for 60-90% of all living organisms. The applied simulation technique is based on the Geant4 Monte Carlo transport code, which shows good agreement with experimental cross sections for dosimetry and nano-dosimetry measurements. The calculations were made for protons and carbon ions with different kinetic energies within a relatively wide range of the Bragg curve and linear energy transfer (LET) values from a few to hundreds of keV/μm. We estimated and compared the distribution of energy deposition events and production of reactive chemical species within nanometric volumes of silicon and water after irradiation. We also performed a microdosimetric calculation to estimate LET distribution and nanodosimetric calculation to analyze cluster distributions of ionizations, excitations, elastic collisions and dissociative attachment for electrons corresponds to an interaction with a nonzero energy deposition.